QUALITY OF WORK LIFE (QWL) EVALUATION AND FACTORS AFFECTING QUALITY OF WORK LIFE (QWL) IN NURSES AT SATKES KODIKLATAL BY CROSS SECTIONAL STUDY - Mega Nurmalasari Wira Putri; Djazuly Chalidyanto (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2020)
ABSTRACT The hospital is a health service business, one of which is based on the principle of trust so that service quality problems, patient satisfaction and patient loyalty are factors that determine its success. Various ways are used by organizations to create competitive advantage. One of the most important aspects in creating competitive advantage is increasing the quality of human resources owned. Quality of Work Life is a concept or management philosophy in the fieldgka improvement in the quality of human resources that has been known since the seventies. By realizing and maintaining a healthy QoWL, it will increase employee job satisfaction, reduce the number of employees leaving, increase productivity and improve nursing care outcomes. Analysis of the QoWL factor was carried out using questionnaire data for 120 nurses in the ER department, outpatient and inpatient care. Analysis of QoWL results for satisfaction is in the dimensions of Control at Work and Stress at Work and for employee dissatisfaction is in the dimensions. between employees. From this analysis, recommendations for improvement and enhancement of the quality of a good work life can be made through stress management, existing workforce analysis. Keywords: Quality of work life, Cross Sectional Study, Satkes Kodiklatal.